2001
DOI: 10.1590/s0034-71082001000100011
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and food habits of the lined seahorse, Hippocampus erectus (Teleostei: Syngnathidae) of Chesapeake Bay, Virginia

Abstract: The reproductive and feeding biology of the lined seahorse, Hippocampus erectus, was studied in Chesapeake Bay. Seahorses are monogamous, and males incubate the eggs received from females in a closed brood pouch (= marsupium). Females do not play any parental care after mating. Total sex ratio and the operational sex ratio was strongly skewed toward females. Males and females had similar number of eggs/embryos and hydrated oocytes, respectively. The number of eggs/embryos found in the male brood pouch varied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 8 publications
(11 reference statements)
5
84
0
5
Order By: Relevance
“…The occasional consumption of insects (ants) observed in this study is unique, and is possibly related to the massive presence of mangrove trees along the margins of the estuary. While Harpacticoida was the principal item consumed by Hippocampus zosterae (Tipton & Bell, 1988), H. subelongatus (Kendrick & Hyndes, 2005) and H. reidi (this study), the other studied seahorse species mostly consumed Cyclopoida copepods, amphipods and caridean shrimps (see Kanou & Kohno, 2001;Kendrick & Hyndes, 2005;Teixeira & Musick, 2001;Burchmore et al, 1984;Woods, 2002). These results highlight the importance of crustaceans as a prey category to seahorses.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The occasional consumption of insects (ants) observed in this study is unique, and is possibly related to the massive presence of mangrove trees along the margins of the estuary. While Harpacticoida was the principal item consumed by Hippocampus zosterae (Tipton & Bell, 1988), H. subelongatus (Kendrick & Hyndes, 2005) and H. reidi (this study), the other studied seahorse species mostly consumed Cyclopoida copepods, amphipods and caridean shrimps (see Kanou & Kohno, 2001;Kendrick & Hyndes, 2005;Teixeira & Musick, 2001;Burchmore et al, 1984;Woods, 2002). These results highlight the importance of crustaceans as a prey category to seahorses.…”
Section: Discussionsupporting
confidence: 58%
“…Reproductive state: IM = immature, OF = ovipositor region flat, OB = ovipositor region bulging, B = brooding, NB = non-brooding. while mid size and larger specimens fed almost exclusively on amphipods (Teixeira & Musick, 2001). Additionally, Tipton & Bell (1988) found an increase in the consumption of amphipods by larger specimens of H. zosterae, despite the dominance of harpacticoid copepods in all size classes, and Kanou & Kohno (2001) reported that juveniles H. mohnikei exhibited a division of prey items between size classes, with the smaller seahorses feeding mainly on cyclopoid copepods smaller than those consumed by larger specimens.…”
Section: Discussionmentioning
confidence: 98%
“…However, the low survivorship of juvenile seahorses and low reproductive efficiency of the broodstock seahorses have restricted seahorse culture for many years (Herald and Rakowicz, 1951;Scarratt, 1995;Wilson and Vincent, 1998;Wong and Benzie, 2003;Lin et al, 2006). Therefore, recent research works have mainly focused on the growth and survivorship of juveniles (Scarratt, 1995;Woods, 2000Woods, , 2003aSheng et al, 2006;Lin et al, 2008), and on broodstock reproduction (Selman et al, 1991;Vincent, 1995;Teixeira and Musick, 2001;Perante et al, 2002;Lin et al, 2006Lin et al, , 2007Faleiro et al, 2008). The effects of illumination, feed ration, stocking density and gender segregation on growth and survival have been examined in Hippocampus abdominalis (Woods, 2000(Woods, , 2003a(Woods, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Strawn (1958) also found that in Hippocampus zosterae from Florida there was an increasing relationship between length of seahorses and the number of eggs contained in the brood pouches of male seahorses, and Texeira & Musick (2001) observed the same trend in Hippocampus erectus from Chesapeake Bay. This correlation is logical given that pouch volume, and hence eggcarrying capacity, increases as males increase in overall size.…”
Section: Discussionmentioning
confidence: 89%
“…zosterae. Texeira & Musick (2001) found non-fertilised eggs frequently in wild H. erectus (i.e., occurring in 50% of males examined and ranging in percentage of total pouch contents from 1.7% to 33%). In captive H. fuscus, Vincent (1990) found that males failed to incubate on average between 9 and 48% of their broods, with lower failure rates in mating pairs that had been together longer.…”
Section: Discussionmentioning
confidence: 90%